2019
DOI: 10.3390/sym11030438
|View full text |Cite
|
Sign up to set email alerts
|

Effects MHD and Heat Generation on Mixed Convection Flow of Jeffrey Fluid in Microgravity Environment over an Inclined Stretching Sheet

Abstract: In this paper, Jeffrey fluid is studied in a microgravity environment. Unsteady two-dimensional incompressible and laminar g-Jitter mixed convective boundary layer flow over an inclined stretching sheet is examined. Heat generation and Magnetohydrodynamic MHD effects are also considered. The governing boundary layer equations together with boundary conditions are converted into a non-similar arrangement using appropriate similarity conversions. The transformed system of equations is resolved mathematically by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…In the study presented in [15], Jeffrey fluid was studied in a microgravity environment. Unsteady two-dimensional incompressible and laminar g-Jitter mixed convective boundary layer flow over an inclined stretching sheet was examined.…”
Section: Methodologies and Usagesmentioning
confidence: 99%
“…In the study presented in [15], Jeffrey fluid was studied in a microgravity environment. Unsteady two-dimensional incompressible and laminar g-Jitter mixed convective boundary layer flow over an inclined stretching sheet was examined.…”
Section: Methodologies and Usagesmentioning
confidence: 99%
“…Rasool et al [6,7] reported on some interesting findings in Marangoni convection of nanofluids involving simple as well as Riga plates with various other important physical parameters, respectively. Some recent and interesting articles can be found in [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and cross references cited therein.…”
Section: Introductionmentioning
confidence: 99%
“…In another attempt, Waqas et al [29] used convective boundary assumption for the flow of Maxwell nanofluid with motile microorganisms. Dero et al [30] captured multiple solutions for bioconvection that involve nanoparticles in the presence of wall blowing and slip features [31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%